Integration of the cognitive and the psychodynamic unconscious. - Epstein, Seymour (American Psychologist, 1994)
Cognitive-experiential self-theory integrates the cognitive and the psychodynamic unconscious by assuming the existence of two parallel, interacting modes of information processing: a rational system and an emotionally driven experiential system. Support for the theory is provided by the convergence of a wide variety of theoretical positions on two similar processing modes; by real-life phenomena—such as conflicts between the heart and the head; the appeal of concrete, imagistic, and narrative representations; superstitious thinking; and the ubiquity of religion throughout recorded history—and by laboratory research, including the prediction of new phenomena in heuristic reasoning. Reprinted by permission of the publisher.